PENGEMBANGAN MEDIA MOBILE LEARNING DALAM PEMBELAJARAN AKSARA LAMPUNG DI SD KELAS II - Ariyani, Farida; Marselinda, Renatalia; Ulfa, Siti Tiara (FKIP Universitas Lampung, 2023)
This development research describes the problem of limited learning media experienced by students in learning the Lampung script at the State Madrasah Ibtidaiyah (MIN). The method used in this research is the research and development (R&D) method. Sources of data used in the form of interviews and observations The results of this research and development are in the form of mobile learning media that can be installed on Android devices. Based on the results of the research and development that have been carried out, the mobile learning media that have been developed are feasible as a medium for learning the Lampung script at the Madrasah Ibtidaiyah Negeri (MIN) Bandarlampung.